Evaluation of Glypican-3 expression in benign and malignant salivary gland tumors - Azadeh Andisheh-Tadbir; Mohammad Javad Ashraf; Ali Goodarzi; Razieh Zare (Journal of Oral Biology and Craniofacial Research)
Introduction: Glypican-3 (GPC3) is involved in regulation of cell proliferation and morphogenesis. It is abundant in embryonic tissue, but limited in most adult tissues. GPC3 deletion or mutation can disturb the balance between cell apoptosis and proliferation, which may result in tumorigenesis. This study aimed to investigate the GPC3 expression in salivary gland tumors (SGTs) and the adjacent non-neoplastic tissues. Methods: This study reviewed 50 samples of salivary tumors from the archive of Khalili Hospital, Shiraz, Iran, including 17 cases of pleomorphic adenoma (PA), 16 cases of mucoepidermoid carcinoma (MEC), and 17 cases of adenoid cystic carcinoma (ACC); as well as a control group of 23 cases of normal salivary gland tissues. GPC3 expression was investigated through immunohistochemistry. Results: GPC3 expression was significantly higher in malignant tumors (MEC and ACC) than in PA, and higher in PA than in the normal salivary glands (P < 0.001). The expression intensity was moderate to strong in malignant tumors and weak to moderate in benign tumors. No strong positivity was observed in normal salivary gland tissues (P < 0.001). Nor was any association detected between the GPC3 expression and intensity with the clinicopathologic parameters. Conclusion: Although GPC3 overexpression was observed at the protein level in SGTs, and its expression was not related with the clinicopathologic factors, the potential use of GPC3 for diagnostic, therapeutic, and prognostic purposes requires further investigations.